2021
DOI: 10.1002/joa3.12637
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of trans‐venous cardiac device extraction using conscious sedation alone—Implications for the post‐COVID‐19 era

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In contrast, patients under deep sedation (DS) will respond purposefully to repeated and painful stimuli, normally without the need for intubation [10]. TLE under conscious sedation (lighter than deep sedation, patients who purposefully respond to verbal or tactile stimulation) alone with diazepam and/or midazolam has been shown to be feasible [11]. DS is common in many other invasive interventions, such as ablation of atrial fibrillation, and has been shown to be safe and feasible [12].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, patients under deep sedation (DS) will respond purposefully to repeated and painful stimuli, normally without the need for intubation [10]. TLE under conscious sedation (lighter than deep sedation, patients who purposefully respond to verbal or tactile stimulation) alone with diazepam and/or midazolam has been shown to be feasible [11]. DS is common in many other invasive interventions, such as ablation of atrial fibrillation, and has been shown to be safe and feasible [12].…”
Section: Introductionmentioning
confidence: 99%